Developing a new anti-sporozoite malaria vaccine - Datoo, MS (2022)
Malaria is one of the leading infectious causes of morbidity and mortality. There was an estimated 241 million malaria cases and 627,000 deaths in 2020 across 85 malaria endemic countries. When compared with data from recent years, this suggests that global progress has stalled, and that malaria mortality is increasing. There is an urgent need to develop new tools to combat this.